An Investigation if TDM for PAM Signals - Qaradaghi, Thoraya M.; Nizamaldin, Shwbow A. (Sulaimani Journal for Pure and Applied Sciences, 2005)
An analog information signals were converted to discrete-analog signals by the process of sampling. A naturally sampled signals were modified to a PAM (Pulse Amplitude Modulation) signal by flattening the pulse tops to give rectangular pulses, PAM signals were multiplexed together by interleaving the samples of the tributary information signals, The resulting TDM (Time Division Multiplexing) signal had narrower pulses, and therefore greater bandwidth, than was neccessary for each tributary signal alone, This paper discusses the using of EWB package to produce time-division multiplexed PAM signals.
Keywords: Sampling; PAM; TDM